Developing fun e-modules for engaging English learning in primary school - Lasim Muzammil; Maria Purnawati; A. Andy; Finda Hikmah Arifani (Research and Development in Education (RaDEn), 2024)
Teaching material modules in English for primary school can be easily obtained as it is already included in the digital era. However, finding appropriate ones for the instructional process for learners whose internet connection is difficult remains low. Therefore, this research aims to produce a valid and feasible English E-module as a learning medium. The ADDIE approach is used, which stands for analysis, design, development, implementation, and evaluation. The study tested validity by material, media, and language validators to determine the quality of the media developed. The results of this study are that the overall average validation of material is 77.2%, media validation is 78.5%, and language validation gets 87.5% with the "Excellent" category. Next, to determine the feasibility of the English E-module researchers analyzed English teachers and students of grade 5A. Results obtained from English teachers got 81.5% and from 5A students got 88.4% with the "Excellent" category. The English E-module as the learning media developed has been valid and feasible. Thus, English teachers for primary school and EFL learners may take advantage to make use of the module. Other researchers should add more skills such as listening by providing audio files and using different levels for the next study.